Upper-Extremity Deep Venous Thrombosis after Whole Blood Donation—A Case Report - Abidoye, Oluseyi; Johnson, Andrew; Cho, Young Min; Ogbuagu, Henry; Choudhury, Hasan; Takegawa, Ryosuke; Hayashida, Kei; Shinozaki, Koichiro; Aoki, Tomoaki; Okuma, Yu; Zanos, Stavros; Zafeiropoulos, Stefanos; Giannis, Dimitrios; Pipolo, Derek O.; Becker, Lance B.; Miyara, Santiago J.; Guevara, Sara; Molmenti, Ernesto P. (International Journal of Angiology, 2022)
Upper-extremity deep venous thrombosis (UEDVT) after whole blood donation is rarely reported. Blood donation has a low rate of complications and is typically safe. A small percentage of blood donors experience donation-related events such as UEDVT, which are extremely rare. We are reporting a rare case of a UEDVT following blood donation. This is an extremely rare event; only five cases were reported to our knowledge. A 22-year-old Caucasian woman with a past medical history of provoked pulmonary embolism completed 6 months of apixaban and negative thrombophilia workup presented to the hospital with complaints of progressive pain and swelling in her right arm. The patient reports donating blood using her right arm in January 2021. Phlebotomy duration for blood donation was approximately 10minutes. She reported pain and swelling several days after blood donation. Subsequently, a duplex ultrasound showed a thrombus in the right brachial vein. The patient was started on apixaban for 6 months. Although most whole blood donors do not experience complications, DVT is a rare complication from whole blood donation with severe consequences. It should be considered in a donor with worsening pain and swelling.
Keywords: upper-extremity deep venous thrombosis; whole blood donation; phlebotomy; Virchow's triad; venous duplex; apixaban; warfarin